ANALISA VEGETASI HUTAN MANGROVE PELABUHAN LEMBAR KABUPATEN LOMBOK BARAT NUSA TENGGARA BARAT - Amir Syarifuddin; Zulharman . (Jurnal Gamma, 2012)
ANALISA VEGETASI HUTAN MANGROVE PELABUHAN LEMBAR KABUPATEN LOMBOK BARAT NUSA TENGGARA BARATAmir Syarifuddin1 & Zulharman21&2 Jurusan Kehutanan, Fakultas Pertanian dan PeternakanUniversitas Muhammadiyah Malange-mail: 1)amir_1958@yahoo.co.idABSTRACTThe research aimed to find out potential of mangrove forest in Pelabuhan Lembar Lombok Barat Residence Nusa Tenggara Barat area. The research was done in Pelabuhan Lembar Lombok Barat Residence Nusa Tenggara Barat area with 183,63 Ha area which was done in July 2011 until July 2012.Method used in measurement and observation of Mangrove vegetation observation using transect/double quarter line with measurement square 20x20 m2 for trees inside measurement square. In measurement square with size 20x20 m2 there made smaller square 10x10 m2 for pole level. While for 5x5 m2 square for pole and 2x2 m2 square for understory.From the research done in Pelabuhan Lembar, there found 5 kinds of 3 different famili: A. marina (Forsk) Vierh, R. apiculata BI, R. mucronata Lmk, R. stylosa Griff, S. alba J.E Smit. In Pelabuhan Lembar area dominated kind was R. apiculata BI and R. stylosa Griff. Vegetation with highest INP value for trees was R. apiculata BI that was 88,8%, for pole kind was R. apiculata BI that was 89,2% and pole variance was R. apiculata BI that was 79,4%.In general, there could be seen zone mangrove forest in Pelabuhan Lembar Lombok Barat Residence Nusa Tenggara Barat area as: close beach zone, R. apiculata BI, R. mucronata Lmk, R. stylosa Griff and S. alba J.E Smit Lamk. Middle zone were A. marina (Forsk) Vierh.According to research done in Pelabuhan Lembar Lombok Barat Residence Nusa Tenggara Barat area, there were Mangrove destruction caused by tritip pest caused damaged in mangrove stand also destruction by people around the beach. That’s why there needed reservation and safety in mangrove forest at Pelabuhan Lembar Lombok Barat Residence Nusa Tenggara Barat area so that mangrove forest could be benefit for people around the beach and Life Environment and Research Institution and another related institution. Key word :Vegetasi, mangrove forests